(untitled) (Journal of Contemporary Philology, 2020)
Linearization and word order are frequently considered to be synonymous terms. Yet, word order can be marked as a subset of linearization as a set, in a sense of setting larger elements at the same level, as a base for the syntax (σύν– together, and τάξις– an ordering), opposed to setting one word within the smaller parts of the sentence (clause, noun phrase, etc.). Traditionally, we say that particles are non-paradigmatic words that do not have their own semantics but they obtain their meaning as part of broader and more complex constructions. The Macedonian norm prescribes that these words should take an initial position in noun phrases (NP) introduced with preposition because they refer to the whole NP. However, we will demonstrate that there are cases in which a particle can take a non-initial position due to the pragmatic motivation (focus on a quantifier) or as a limitation/modification of the qualitative modifier in such cases in which the centre of the NP is already qualitatively modified.